IDENTIFIKASI STAKEHOLDER UNTUK MENYUSUN DESAIN KOLABORASI DALAM KESEHATAN MATERNAL (Studi Kasus Kabupaten Bantul) - Teguh Budi Prasetya; Prihastuti; Sylvi Wafda Nur Amellia (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2025)
Maternal health serves as a key indicator in assessing the quality of healthcare services and the success of a country's health development efforts. It encompasses not only the safety of mothers during pregnancy, childbirth, and the postpartum period, but also reflects the accessibility, effectiveness, and coordination within the healthcare system involving multiple stakeholders. Despite various intervention efforts, maternal mortality remains a significant challenge in Indonesia. According to the 2023 Indonesian Health Survey (SKI), the maternal mortality ratio (MMR) in Indonesia stands at 189 per 100,000 live births, which is still above the national target set in the 2020–2024 National Medium-Term Development Plan (RPJMN), namely 183 per 100,000 live births. A thorough identification of maternal health stakeholders is essential not only to understand the extent of national support for maternal health issues, but also to design effective stakeholder collaboration to accelerate the achievement of maternal health targets. This case study in Bantul Regency, Special Region of Yogyakarta (DIY), identifies at least seven potential stakeholders for collaboration: the District Health Office, hospitals, community health centers (Puskesmas), the Office of Population and Family Planning, village governments, social organizations, higher education institutions, and the business sector. Each of these stakeholders has a distinct and valuable role to play.